OPTIMIZATION STUDY OF GATE OPERATION RULE IN CIAWI DAM AS FLOOD CONTROL FUNCTION (Jurnal Teknik Sipil, 2022)
The purpose of this research is to find out the effectiveness of operating gate on the design of flood routing and provide an alternative outlet operation gate for maximum flood reduction. The location of the research area is the Ciawi Dam watershed with an area of ​​88.50 km2, a river length of ±16.70 km and an average river slope of 5.60%. This research data is based on climatological data, low discharge data, flood hydrograph, and dam and reservoir engineering data. In addition, there are supporting data to perform calculations and analyzes, such as flood discharge data, elevation curve – reservoir volume and layout of the dam and its complementary buildings, existing operating patterns, and regional socio-economic data studies. The method used is to calculate flood routing of the capital flow curve at the outlet operation gate. The simulation is carried out using a design flood hydrograph so that optimal flood reduction can be determined by the outlet operation gate. Based on the results of the maximum reduction in the design of the reservoir operation dam design without utilizing the conduit gate as a flood control function, the researchers optimized the door operation pattern to increase the flood reduction capacity (optimization) of the Ciawi Dam. The result of the calculation and analysis is that the flood return period (Q25 th) is able to reduce flooding by 54.64%; flood return period (Q50 yr.) is able to reduce flooding by 45.21%; flood return period (Q100 yr.) is able to reduce flooding by 38.06%; flood return period (Q500 yr.) is able to reduce flooding by 38.50%; and the flood return period (Q1000 yr.) was able to reduce flooding by 33.22%. So, it can be concluded that by utilizing the bottom outlet gate as a flood discharge regulation, the benefits obtained are 42.27% (at Q 25 yrs.) from the pattern of dam operation without gate regulation.